The Nepali Perspectives on International News Coverage - Basnet, Dil Bahadur (Communication Journal, 2022)
This paper presents a reflection on the colours of headlines in international news coverage in the Nepali English dailies. Headlines have the power of attracting and repulsing audiences on the ground of their professional appearance especially, in this context, relating to their different colours. It is important to note that audiences complete their journey in three ways: tasting, gulping, and biting and processing titles that can zest things up. It is actually a portrayal of professional insight into the multi-dimensional messaging of information through headlines crafted in the context of international communication in Nepal. There is still a need for other empirical research on headlines from several other perspectives.